A política de assentamento rurais executada pelo INCRA: os gargalos na implantação e acompanhamento dos projetos de assentamento - Figueredo, Cleria (2019)
The constant changes in laws, rules and procedures that govern the Agrarian Reform Policy, the ups and downs that changes in governments bring about, leading to the discontinuity of actions and programs, the successive TCU Judgments, which culminated in the interruption of INCRA various actions, and the results of the final titling of the lots in the settlement projects, point to a fragile or inadequate management of the Rural Settlement Policy. In this approach, the research problem has as its guiding question: What are the bottlenecks in the administrative process of the Rural Settlement Policy that may be contributing to these results. The general objective is to analyze the administrative process of the Rural Settlement Policy, in order to identify the implementation bottlenecks, considering the legislation that guides the policy focusing on the three actions that serve as the basis of the policy, the creation, registration, selection and approval. Of the beneficiaries, the occupational supervision of the lots and the definitive titling, with the information raised in the Regional Superintendence of Santa Catarina – SR (10)/SC. As methods were used the bibliographic researches, approaching, the theories related to public policies, Agrarian Reform and Rural Settlements, Internal Control and Process Management, as well as documentary research and survey, in addition to the case study with techniques of non-participant observation and semi-structured interviews complement the research. The results point to the confirmation of the guiding question, the existence of bottlenecks in the operational management of the policy, generated by the noncompliance with regulations, the lack of organization and planning of actions, lack of human resources, precarious information technology, Obsolete systems such as Sipra and political interference. This research concluded that there is a need for a change in the operational management of INCRA, in order to correct problems that are affecting the results of public policy, implementing process management, seeking to modernize its systems and introducing technologies that support and organize activities performed.